Lappisches Wörterbuch, nach den Dialekten - Nielsen, Konrad, 1875-1953. (Helsingfors, 1913)
A complete ed. (in 3 v.) was issued in 1932 under title: Lappisk ordbok (added t.p.: Lapp dictionary) No more published. Cover title. Mode of access: Internet.